Research on the Health Economic Burden Compensation Scheme for the Elderly in Multi-Level Medical Security System - Liu, Yuqi (International Journal of Public Health and Medical Research, 2025)
With the global aging trend, the elderly now bear a significant health economic burden. This study aims to explore effective compensation methods within a multi-tiered healthcare system for this group, focusing on China’s aging society and medical security reform. Despite extensive research, gaps remain in elderly-specific compensation mechanisms. Utilizing health economics and a multi-level medical security framework, this study employs advanced techniques (e.g., machine learning) to assess elderly medical needs and costs, proposing scientific compensation strategies. Expected outcomes include reduced out-of-pocket costs, higher reimbursement rates, and broader insurance coverage, supporting policy formulation. The study also analyzes regional, economic impacts on elderly medical expenditures to ensure fair, efficient compensation.